2018
DOI: 10.1371/journal.pone.0199891
|View full text |Cite
|
Sign up to set email alerts
|

Long term effect of primary health care training on HIV testing: A quasi-experimental evaluation of the Sexual Health in Practice (SHIP) intervention

Abstract: BackgroundTo examine the effect of Sexual Health in Practice (SHIP) training for general practitioners (GPs) on HIV testing rates in Haringey, a deprived area of London, UK, with a population of over 250,000 and HIV prevalence of 0.7% (in 2014). SHIP is an educational intervention delivering peer-developed and peer-led face-to-face training to improve quality of sexual and reproductive health (SRH) care.MethodsWe carried out a quasi-experimental study of intervention effects across 52 GP practices (2008–2016).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Other sexual health testing educational interventions have been undertaken in the UK [35, 42]. HIV testing rates increased in general practices receiving a multifaceted educational intervention (Sexual Health in Practice -SHIP) in an extremely high diagnosed HIV prevalence area in London [35] and that these were sustained over 8 years [43]. This study used five rounds of training over a 24-month period which differs to the one-off training used in the current study, potentially illustrating the benefits of repeated training sessions over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other sexual health testing educational interventions have been undertaken in the UK [35, 42]. HIV testing rates increased in general practices receiving a multifaceted educational intervention (Sexual Health in Practice -SHIP) in an extremely high diagnosed HIV prevalence area in London [35] and that these were sustained over 8 years [43]. This study used five rounds of training over a 24-month period which differs to the one-off training used in the current study, potentially illustrating the benefits of repeated training sessions over time.…”
Section: Discussionmentioning
confidence: 99%
“…The policy has a 96% acceptance rate in antenatal settings and has had a dramatic effect on reducing the number of women with undiagnosed HIV post-delivery and mother-to-child transmission [32]. Studies promoting IC-based testing [43] have shown a relatively low increase in testing compared to HIV screening studies such as the RHIVA trial of rapid HIV testing [31], although positivity rates tend to be higher in targeted interventions [10].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SHIP (Sexual Health in Practice), a multi-component educational intervention, achieved significantly increased HIV testing rates in general practices in a high-HIV prevalence area in London [25, 28]. Unlike the current intervention, SHIP involved two afternoons of training for GPs (and three for nurses) [25].…”
Section: Discussionmentioning
confidence: 99%
“…The guidance recommends offering a test to all new practice patients [23] and to patients presenting with HIV ICs [19]. However, barriers to HIV testing experienced by HCPs include gaps in knowledge and training needs [17, 24, 25], anxiety or a lack of confidence to offer a test, concern about negative patient response [25, 26] and, privacy and confidentiality issues [25, 26]. These barriers and the opportunity to diagnose HIV through improved recognition of HIV ICs indicate a role for educational interventions to encourage increased testing [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation